The Torque Teno Virus Titer in Saliva Reflects the Level of Circulating CD4+ T Lymphocytes and HIV in Individuals Undergoing Antiretroviral Maintenance Therapy - Honorato, Layla; Witkin, Steven S.; Mendes-Correa, Maria Cássia; Conde Toscano, Ana Luiza Castro; Linhares, Iara Moreno; de Paula, Anderson Vicente; Paião, Heuder Gustavo Oliveira; de Paula, Vanessa Salete; Lopes, Amanda de Oliveira; Lima, Silvia Helena; Raymundi, Vanessa de Cássia; Ferreira, Noely Evangelista; et al. (Frontiers in Medicine, 2022)
Introduction: Torque teno virus (TTV) is a nonpathogenic virus present in body fluids. Its titer in the circulation increases in association with immune suppression, such as in HIV-infected individuals. We evaluated if the TTV titer in saliva from HIV-positive individuals undergoing antiretroviral therapy (ART) was related to the circulating CD4+ T lymphocyte concentration and the HIV titer. Methods: Saliva was collected from 276 asymptomatic individuals undergoing ART, and an additional 48 individuals positive for AIDS-associated Kaposi’s Sarcoma (AIDS-KS). The salivary TTV titer was measured by gene amplification analysis. The circulating CD4+ T lymphocyte and HIV levels were obtained by chart review. Results: TTV was detectable in saliva from 80% of the asymptomatic subjects and 87% of those with AIDS-KS. In the asymptomatic group the median log10 TTV titer/ml was 3.3 in 200 males vs. 2.4 in 76 females (p <0.0001). TTV titer/ml was 3.7 when HIV was acquired by intravenous drug usage, 3.2 when by sexual acquisition and 2.4 when blood transfusion acquired. The salivary TTV titer was inversely correlated with the circulating CD4+ T lymphocyte level (p <0.0001) and positively correlated with the circulating HIV concentration (p = 0.0005). The median salivary TTV titer and circulating HIV titer were higher, and the CD4+ count was lower, in individuals positive for AIDS-KS than in the asymptomatic subjects (p <0.0001). Conclusion: The TTV titer in saliva is a potential biomarker for monitoring immune status in individuals undergoing ART.